Impact of caregiver overnight stay on postoperative outcomes. Issue 1 (11th December 2019) - Griffin, Susan; McGrath, Leigh; Chesnut, Gregory T.; Benfante, Nicole; Assel, Melissa; Ostrovsky, Aaron; Levine, Marcia; Vickers, Andrew; Simon, Brett; Laudone, Vincent
Abstract : Purpose: The purpose of this paper is to determine the impact of having a patient-designated caregiver remain overnight with ambulatory extended recovery patients on early postoperative clinical outcomes. Design/methodology/approach: This was a retrospective cohort study of patients undergoing surgery requiring overnight stay in a highly resourced free-standing oncology ambulatory surgery center. Postoperative outcomes in patients who had caregivers stay with them overnight were compared with outcomes in those who did not. All other care was standardized. Primary outcomes were postoperative length of stay, hospital readmission rates, urgent care center (UCC) visits within 30 days and perioperative complication rates. Findings: Among patients staying overnight, 2, 462 (57 percent) were accompanied by overnight caregivers. In this group, time to discharge was significantly lower. Readmissions (though rare) were slightly higher, though the difference was not statistically significant ( p =0.059). No difference in early (<30 day) complications or UCC visits was noted. Presence of a caregiver overnight was not associated with important differences in outcomes, though further research in a less well-structured environment is likely to show a more robust benefit. Caregivers are still recommended to stay overnight if that is their preference as no harm was identified. Originality/value: This study is unique in its evaluation of the clinical impact of having a caregiver stay overnight with ambulatory surgery patients. Little research has focused on the direct impact of the caregiver on patient outcomes, especially in the ambulatory setting. With increased adoption of minimally invasive surgical techniques and enhanced recovery pathways, a larger number of patients are eligible for short-stay ambulatory surgery. Factors that impact discharge and early postoperative complications are important.